The Correlation of the Limitations of Movement of the Shoulder Joint with the Functional Ability of Frozen Shoulder Patients at the Medical Rehabilitation Institute Dr. Mohammad Hoesin Palembang - Sintia, Ine; Nyimas Fatimah (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background: Frozen shoulder is a condition of the shoulder joint that experiences inflammation, pain, adhesions, atrophyand shortening of the joint capsule resulting in limited motion. In frozen shoulder patients, the limited range of motion ofthe shoulder joint can affect and reduce functional ability. This study aims to analyze the correlation between the limitedarea of motion of the shoulder joint with the functional ability of frozen shoulder patients at the Medical RehabilitationInstallation Dr. Mohammad Hoesin Palembang. Methods: This study was an observational analytic study, correlationtest, with a cross sectional design. There were 29 frozen shoulder patients who met the inclusion criteria in the MedicalRehabilitation Installation Dr. Mohammad Hoesin Palembang in November 2018 was taken as a sample using consecutivesampling techniques. Functional ability was assessed using the quickDASH questionnaire and the area of motion wasmeasured using a goniometer, then analyzed. Results: The results of the correlation test showed significant resultsbetween functional abilities and the area of motion of the shoulder joints. Active flexion (p = 0.000; r = -0.669), activeextension (p = 0.004; r = -0.520), active abduction (p = 0.000; r = -0.663), active adduction (p = 0.022; r = -0.423 ), passiveflexion (p = 0.001; r = -0.589), passive extension (p = 0.002; r = -0.543), passive abduction (p = 0.000; r = -0.676), passiveadduction (p = 0.038; r = -0.388). Conclusion: There is a significant correlation between limited joint motion andfunctional ability in frozen shoulder patients at the Medical Rehabilitation Installation of Dr. Mohammad HoesinPalembang